Examining food wastage, cash handling and cost control practices: the case of food and beverage outlets in Malaysia - Zainol, Noor Azimin; Ahmad, Rozila; Rashid Radha, Jasmine Zea Raziah Radha; Ideris, Muhammad Shah Kamal (RMP Publications, 2017)
Background: The food and beverage industry in Malaysia is foreseen to have a bright future as increasing new comers emerge in the market. As competition is getting intense, there is a growing need to understand how food and beverage outlets make profits through an important aspect, but seldom neglected academically, which is cost control measures. Objective: This paper addresses one business strategy to making profit that is by minimising costs, via imposing cost control measures through daily operations. In particular, issues regarding controlling of food and beverage costs are the prime concern in the paper. Little research has been done in understanding cost control issues, particularly in the case of food and beverage outlets in Malaysia hence, an exploratory study is deemed feasible to investigate cost control measures being practiced in their daily operations. What are cost control practices being applied needs exploration whilst other areas that need further investigation includes food wastage and cash handling procedures. Qualitative approach via semi structured interview protocols are being conducted on 30 foodservice outlet managers around the northern part of Malaysia. Results: The findings revealed that the majority of managers acknowledge that there were awareness on cost control measures in their daily operations however these are based on the routine experience of running their operations. The implementation of control procedures are still unbalanced and require improvements. Conclusion: This exploratory study has surfaced the need to cultivate the correct application of cost control measures in food and beverage outlets’ operations in order to remain competitive in the business.